Copper, Magnesium and Selenium Levels in Serum Samples of Male Patients with Type 2 Diabetes Mellitus - Ifeanyichukwu Martin Ositadinma; Ngwu Amauche Martina (Archives of Current Research International, 2020)
Background: Trace elements are known to enhance the complete function of the immune system; avert uncontrolled expression and synthesis of inflammatory cytokines. The aim of this study was to determine the levels of Copper, magnesium, selenium in male individuals with type 2 diabetes mellitus. Study Design: Prospective cohort study. Place and Duration of Study: Medical outpatient clinic and Chemical Pathology Laboratory both of Enugu State University of Science and Technology Teaching Hospital, between January and December 2016. Methodology: Forty male individuals with type 2 diabetes mellitus and forty apparently healthy male individuals within the age range of 45 - 75 years were recruited for this study. Glycated haemoglobin (HbA1c), fasting blood glucose (FBG), trace elements (copper, magnesium and selenium) was measured at six months interval. Results: The mean values of Cu, Mg, Se were significantly lower at pre-treatment compared to apparently healthy control values (18.40 +/- 5.25 vs 95.16 +/- 30.32 µg/dl, 1.23+/- 0.16 vs 1.51+/- 0.09 mg/dl and 268.47+/-54.32 vs 349.63+/- 32.95 µg/l respectively) (p= <0.001, <0.001 and <0.001 respectively). At 6 month into treatment in comparison to pre-treatment values, there were significant decreases in HbA1c and Mg (5.76+/-0.50 vs 9.74+/-1.25 %, 0.26+/-0.02 vs 1.23+/-0.16 mg/dl respectively) (p= <0.001, <0.001 respectively). Conclusion: The levels of copper and magnesium were lower at pre-treatment, while magnesium was lowest at 6 month into treatment. In this study there is continuous increase in serum selenium levels during the treatment period.